The Hypoxic Room System
The patented Hypoxic Room System, or HRS, developed by Hypoxico Inc., is an extension of the time-proven hypoxic training method. It comes as a 1- or 2-user softwall enclosure (the Standard System), or can be installed in any existing room or enclosure, providing an active exercise environment for the professional athlete, sports clinic, spa and health-and-fitness club. The oxygen-depleted environment HRS in the HER is the same you would find at an elevation of 8,500 ft, such as in the Rockies. Treadmills, stationary bikes, punching bags and other equipment can be used inside the HRS.